Regulatory Phosphorylation of Ikaros by Bruton's Tyrosine Kinase - Ma, Hong; Qazi, Sanjive; Ozer, Zahide; Zhang, Jian; Ishkhanian, Rita; Uckun, Fatih M. (PloS one, 2013)
Diminished Ikaros function has been implicated in the pathogenesis of acute lymphoblastic leukemia (ALL), the most common form of childhood cancer. Therefore, a stringent regulation of Ikaros is of paramount importance for normal lymphocyte ontogeny. Here we provide genetic and biochemical evidence for a previously unknown function of Bruton's tyrosine kinase (BTK) as a partner and posttranslational regulator of Ikaros, a zinc finger-containing DNA-binding protein that plays a pivotal role in immune homeostasis. We demonstrate that BTK phosphorylates Ikaros at unique phosphorylation sites S214 and S215 in the close vicinity of its zinc finger 4 (ZF4) within the DNA binding domain, thereby augmenting its nuclear localization and sequence-specific DNA binding activity. Our results further demonstrate that BTK-induced activating phosphorylation is critical for the optimal transcription factor function of Ikaros.